Pendampingan Emosi dan Kemampuan Mengelola Emosi pada Karyawan yang Mengalami Perubahan Organisasi - Nur Afni Indahari Arifin; Rasimin B. Sanmustari (Universitas Islam Indonesia, 2009)
Organizational change causes various reactions toward organizational members, include emotional reaction- The aim of this research is to improve the emotional management ability on organizational members that get into organizational change through emotional coaching method. Participants in this research were three employees that get organizational change. The experiment design used Small n Experiment with ABA design. Research participants followed the designed meeting schedule for a month. The intervention effectiveness measured by Resistance to Change Scale (Oreg, 2003). The results showed that emotional coaching significantly able to improve employee emotional management ability toward organizational change.Keywords:Â Â emotional coaching, emotional management, organizational change